A Socio-Cultural Analysis of Practitioner Perspectives on Implementation of Evidence-Based Practice in Special Education. (May 2016) - Hudson, Roxanne F.; Davis, Carol A.; Blum, Grace; Greenway, Rosanne; Hackett, Jacob; Kidwell, James; Liberty, Lisa; McCollow, Megan; Patish, Yelena; Pierce, Jennifer; Schulze, Maggie; Smith, Maya M.; et al.
Despite the central role "evidence-based practice" (EBP) plays in special education agendas for both research and policy, it is widely recognized that achieving implementation of EBPs remains an elusive goal. In an effort to better understand this problem, we interviewed special education practitioners in four school districts, inquiring about the role evidence and EBP played in their work. Our data suggest that practitioners' responses to policies that press for increased use of EBP are mediated by a variety of factors, including their interpretations of the EBP construct itself, as well as the organizational conditions of their work, and their access to relevant knowledge and related tools to support implementation. We interpret these findings in terms of their implications for understanding the problem of implementation through a more contextual and ecological lens than has been reflected in much of the literature to date.